Applications of nanocomposites - Aliofkhazraei, Mahmood (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
The first volume of this book covered Section I: Introduction to Nanocomposites Fabrication and Section II: CNT and Graphene Nanocomposites. The present second volume covers Section III: Recent Applications of Nanocomposites. The second volume aims to provide a guide for different applications of modern nanocomposites especially those fabricated by carbon nanotubes and graphene. The book makes a comparative study of fiber-reinforced composites which have been embedded into the matrix with nanocomposites containing nanotubes in place of fibers. The main topics of this volume are: Electrochemical Properties of Nanoporous Based Materials, Fabrication and Application of Graphene Oxide-based Metal and Metal Oxide Nanocomposites, Electrochemical Sensors/Biosensors Based on Carbon Aerogels/Xerogels, Advances in Nanobiocatalysis: Strategies for Lipase Immobilization and Stabilization, Metal Oxide Based Heterojunction Nanoscale Materials for Chemiresistive Gas Sensors, Recent Advances in Polymer Nanocomposite Coatings for Corrosion Protection, Recent Advances in the Design of Nanocomposite Materials via Laser Techniques for Biomedical Applications, Carbonaceous Nanostructured Composites for Electrochemical Power Sources: Fuel Cells, Supercapacitors and Batteries, Bismuth Vanadate Based Nanostructured and Nanocomposite Photocatalyst Materials for Water Splitting Application.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science; Nanocomposites (Materials)